Thermal IR satellite data application for earthquake research in Pakistan. (May 2018) - Barkat, Adnan; Ali, Aamir; Rehman, Khaista; Awais, Muhammad; Riaz, Muhammad Shahid; Iqbal, Talat
Abstract: The scientific progress in space research indicates earthquake-related processes of surface temperature growth, gas/aerosol exhalation and electromagnetic disturbances in the ionosphere prior to seismic activity. Among them surface temperature growth calculated using the satellite thermal infrared images carries valuable earthquake precursory information for near/distant earthquakes. Previous studies have concluded that such information can appear few days before the occurrence of an earthquake. The objective of this study is to use MODIS thermal imagery data for precursory analysis of Kashmir (Oct 8, 2005; Mw 7.6; 26 km), Ziarat (Oct 28, 2008; Mw 6.4; 13 km) and Dalbandin (Jan 18, 2011; Mw 7.2; 69 km) earthquakes. Our results suggest that there exists an evident correlation of Land Surface Temperature (thermal; LST) anomalies with seismic activity. In particular, a rise of 3–10 °C in LST is observed 6, 4 and 14 days prior to Kashmir, Ziarat and Dalbandin earthquakes. In order to further elaborate our findings, we have presented a comparative and percentile analysis of daily and five years averaged LST for a selected time window with respect to the month of earthquake occurrence. Our comparative analyses of daily and five years averaged LST show a significant change of 6.5–7.9 °C for Kashmir, 8.0–8.1 °C for Ziarat and 2.7–5.4 °C for Dalbandin earthquakes. This significant change has high percentile values for the selected events i.e. 70–100% for Kashmir, 87–100% for Ziarat and 84–100% for Dalbandin earthquakes. We expect that such consistent results may help in devising an optimal earthquake forecasting strategy and to mitigate the effect of associated seismic hazards.